2020
DOI: 10.2196/15378
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Interventions for Sexual Health Promotion for Adolescents and Young Adults on the Internet: Systematic Review

Abstract: Background The World Health Organization recommends the development of participatory sexuality education. In health promotion, web-based participatory interventions have great potential in view of the internet’s popularity among young people. Objective The aim of this review is to describe existing published studies on online participatory intervention methods used to promote the sexual health of adolescents and young adults. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 49 publications
1
33
0
1
Order By: Relevance
“…Ten studies (50%) dealt with school-based interventions [ 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], 9 (45%) referred to online interventions [ 46 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and 1 (5%) was a review of blended learning programs [ 64 ]. In total 491 studies were included in the 20 reviews covered by the present RoR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies (50%) dealt with school-based interventions [ 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], 9 (45%) referred to online interventions [ 46 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and 1 (5%) was a review of blended learning programs [ 64 ]. In total 491 studies were included in the 20 reviews covered by the present RoR.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were conducted in high-income economies following the World Bank classification [ 65 ], including US samples in 16 of the 20 studies, although there are two studies in which the country of the sample is not identified [ 51 , 52 ]. Most of the studies evaluating interventions in school settings also include developing countries (low- and middle-income economies) [ 45 , 47 , 50 , 52 , 53 , 55 ], as is also the case in three reviews of online interventions [ 46 , 61 , 62 ] (see Table A2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to be effective, such programmes designed to effect change in behaviour and attitudes need to be informed by recognized theoretical and behaviour change models [ 6 ]. Specifically, in relation to sexual health, the importance of sexual health improvement and prevention activities are recommended [ 7 , 8 ]. From a sexual health perspective, there has been increased attention on issues including sexual transmitted infections (STIs) [ 9 ], HIV and AIDS [ 10 ], youth pregnancy [ 11 ], contraception [ 12 ] and gender-based violence [ 13 ].…”
Section: Introductionmentioning
confidence: 99%